O concretismo no Ceará: neovanguarda em trânsito - Damasceno, Kedma Janaina Freitas (2024)
The Concrete Poetry movement in Brazil had its peak mainly between the second half of the 1950s and of the early 1960s. The constructivist, objective, anti-discursive and visual character of the poem began to be initially postulated by the brothers Haroldo and Augusto de Campos and their friend Décio Pignatari, who formed the Noigandres Group. In a developmental period, in search for the country's industrial, economic and urban growth, the abstractionism, both in the visual arts and in the poetry, found an adequate space. The first demonstrations took place in São Paulo (1956) and Rio de Janeiro (1957), states that were more economically developed and, therefore, supposedly more prepared to receive the proposed artistic and cultural innovations. However, the objective of this work is to outline a historical overview of the local concretist movement, presenting how this poetic neo-avant-garde came about in Ceará, a state considered peripheral, little industrialized and, therefore, perceived as less attuned to with the ideas of the modernity, of the industrialization and of the progress, so dear and opportune to Concretism. It will be seen that, in Fortaleza, a group of poets adhered to concretist ideas, maintained contact with groups from the Southeast and held two Concrete Art exhibitions in the capital of Ceará (1957 - at the Clube do Advogado and 1959 - at IBEU), in addition to other smaller exhibitions held at events promoted by some courses at the University of Ceará. Even if less committed to formal rigor, compared to the concretists of São Paulo, the people from Ceará had significantly contributed to the movement, since, in addition to the exhibitions held, they gave interviews, exchanged correspondence, promoted lectures and wrote theoretical texts about the movement in the state. The research work is constructed through the analysis of theoretical-critical studies about that movement, as well as poetic texts and newspaper articles of the time, always seeking to maintain a dialogue with the time and the space of these productions. Authors such as Antonio Candido ([1959] 2017), Pierre Bourdieu (1996), Peter Bürger (2008), Gonzalo Aguilar (2005), Iumna Simon (1982), among others, assist as a theoretical and methodological basis in the composition of this work. In addition to bibliographical research, field research was also undertaken through visits to some significant spaces for the movement, “Conversations/Interviews” with also representative people and research in local newspapers of the time to ratify the thesis that the Concretism of Ceará, despite criticism and a certain erasure, contributed effectively to the national movement, therefore leaving a legacy that resonates to this day.